DARI MEJA BIROKRASI KE LAYAR DIGITAL: TRANSFORMASI ADMINISTRASI PUBLIK MENUJU PELAYANAN YANG RESPONSIF DAN AKUNTABEL DI INDONESIA - Sudirman Rumakeffing (Journal of Innovation Research and Knowledge, 2026)
Bureaucratic reform and digital transformation have become two key issues in efforts to realize efficient, transparent, and accountable public services in Indonesia. This article aims to comprehensively examine how digitalization influences public administration practices, ranging from changes in bureaucratic work patterns and application-based service innovations to the implementation challenges faced by local governments. This study employs a literature review approach by examining various journal articles, textbooks, and prior research relevant to public administration, bureaucratic reform, and digital-based public services. The findings indicate that digital transformation contributes positively to improving the efficiency and quality of public services, as reflected in innovations such as digital population identity applications and integrated online service systems. Nevertheless, the success of this transformation still faces several structural challenges, including the readiness of human resources, technological infrastructure gaps between regions, and the consistency of regulations supporting community participation. This article recommends the need for synergy between bureaucratic governance improvement, strengthening apparatus capacity, and expanding public digital literacy so that the transformation of public administration can proceed sustainably and inclusively.